THE USE OF NOUN PHRASE IN SCIENTIFIC SENTENCE - WENI AYU SUNITA ZANDROTO; NURAINI ADE PUTRI LUBIS; WANAPRI PANGARIBUAN; YUNIARTO MUDJISUSATYO (State University of Medan, 2024)
The purpose of this research is to identify the types and patterns of the noun phrase. The aim of this research is to identify the types and patterns of word combinations that form noun phrases in journal articles published by BJA educational article with the title